Indium tin oxide coated PET film contactless conductivity detector for microchip capillary electrophoresis. Issue 12 (21st June 2015) - Yan, Xingxing; Liu, Wenfang; Yuan, Yu; Chen, Chuanpin
<x xml:space="preserve">Abstract</x> Low-cost ITO coated PET film contactless conductivity detector with microchip electrophoresis for the determination of stimulated samples of heavy metal ions.